Immersions in the metastable dimension range via the normal bordism approach - Biasi, C.; Goncalves, D. L.; Libardi, AKM (Elsevier B.V., 2001)
Let f : M --> N be a continuous map between two closed n-manifolds such that f(*): H-*(M, Z(2)) --> H-* (N, Z(2)) is an isomorphism. Suppose that M immerses in Rn+k for 5 less than or equal to n < 2k. Then N also immerses in Rn+k. We use techniques of normal bordism theory to prove this result and we show that for a large family of spaces we can replace the homolog condition by the corresponding one in homotopy. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: normal bordism; immersion of manifold; localization; group action; nilpotent space